การพัฒนาคุณภาพโรงพยาบาลเพื่อการรับรองคุณภาพโรงพยาบาลระดับสากล - วนิดา แพร่ภาษา (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The purpose of this qualitative research is to explore the quality development of hospital for international accreditation. Thirteen participants included nurse supervisor, nurse management team, deputy supervisor and other employees involved in the JCI accreditation in a selected hospital. Data collection was employed by using in-depth interview and field-note. Coding and constant comparative method were used as data analysis. The finding of the quality development for international accreditation were 5 phases as follows: 1. Preparing phase including (1) setting hospital policy (2) delegating functional teams (3) studying JCI standard and (4) training staff . 2. Developing phase including (1) training and practicing and (2) applying to work. 3. Preparing accredited phase including (1) auditing by surveyors (2) correcting mistakes (3) re-auditing by surveyors and (4) preparing for accreditation. 4. Certifying phase including (1) accrediting by a JCI team and (2) being accredited. 5. Maintaining phase including (1) checking for JCI standard (2) working on quality and (3) giving motivation.